Healthcare access for asylum seekers and refugees in England: a mixed methods study exploring service users' and health care professionals' awareness. (23rd October 2019) - Tomkow, Louise J; Kang, Cara Pippa; Farrington, Rebecca L; Wiggans, Ruth E; Wilson, Rebecca J; Pushkar, Piyush; Tickell-Painter, Maya C; Lee, Alice R; Whitehouse, Emily R; Mahmood, Nadia G; Lawton, Katie M; Lee, Ellen C
Abstract: Background: With the aim of decreasing immigration, the British government extended charging for healthcare in England for certain migrants in 2017. There is concern these policies amplify the barriers to healthcare already faced by asylum seekers and refugees (ASRs). Awareness has been shown to be fundamental to access. This article jointly explores (i) health care professionals' (HCPs) awareness of migrants' eligibility for healthcare, and (ii) ASRs' awareness of health services. Methods: Mixed methods were used. Quantitative survey data explored HCPs' awareness of migrants' eligibility to healthcare after the extension of charging regulations. Qualitative data from semi-structured interviews with ASRs were analyzed thematically using Saurman's domains of awareness as a framework. Results: In total 514 HCPs responded to the survey. Significant gaps in HCPs' awareness of definitions, entitlements and charging regulations were identified. 80% of HCP respondents were not confident defining the immigration categories upon which eligibility for care rests. Only a small minority (6%) reported both awareness and understanding of the charging regulations. In parallel, the 18 ASRs interviewed had poor awareness of their eligibility for free National Health Service care and suitability for particular services. This was compounded by language difficulties, social isolation, frequent asylum dispersal accommodation moves, and poverty. Conclusion: This study identifies significant confusion amongst both HCP and ASR concerning eligibility and healthcare access. The consequent negative impact on health is concerning given the contemporary political climate, where eligibility for healthcare depends on immigration status.